Gambaran Disfungsi Diastolik pada Pasien Hipertrofi Ventrikel Kiri (LVH) Menggunakan Ekokardiografi - Laksono, Sidhi; Sartika, Divina Rana (Viva Medika, 2022)
In cardiac patients with prolonged hypertension, it can increase the occurrence of diastolic dysfunction or systolic dysfunction which ultimately causes heart failure. LVH is an increase in left ventricular mass caused by thickening of the left ventricular wall, an increase in left ventricular volume or both. The purpose of this study was to determine the description of diastolic dysfunction in LVH patients using echocardiography at Hasna Medika Hospital Cirebon. The author used a descriptive method on 60 LVH patients as research subjects with the majority of women as many as 40 (67%). The time of the study was carried out in May-June 2021. Based on the results of the study, it was found that concentric LVH was the most common with 56 people (93%), remodeling concentric LVH with 2 people (3%), and eccentric with 2 people (3 %). In subjects with decreased diastolic dysfunction can be seen from the E/A. Of the 60 subjects in this study, 39 people had decreased LV function. There were 39 people with grade 1 diastolic dysfunction, 2 people with grade 2 diastolic dysfunction, and no grade 3 diastolic dysfunction found. The conclusion was that concentric LVH was found in 93% of the total sample, remodeling concentric in 3%, and eccentric in 3%